Response of micro- and macrovascular endothelial cells to starch-based fiber meshes for bone tissue engineering - Santos, M. I. (2007)
The establishment of a functional vasculature is as yet an unrealized milestone in bone reconstruction therapy. For this study, fibermesh scaffolds obtained from a blend of starch and poly(caprolactone) (SPCL), that have previously been shown to be an excellent material for the proliferation and differentiation of bone marrow cells and thereby represent great potential as constructs for bone regeneration, were examined for endothelial cell (EC) compatibility. To be successfully applied in vivo, this tissue engineered construct should also be able to support the growth of ECs in order to facilitate vascularization and therefore assure the viability of the construct upon implantation. The main goal of this study was to examine the interactions between ECs and SPCL fiber meshes. Primary cultures of HUVEC cells were selected as a model of macrovascular cells and the cell line HPMEC-ST1.6R as a model for microvascular ECs. Both macro- and microvascular ECs adhered to SPCL fiber-mesh scaffolds and grew to cover much of the available surface area of the scaffold. In addition, ECs growing on the SPCL fibers exhibited a typical morphology, maintained important functional properties, such as the expression of the intercellular junction proteins, PECAM-1 and VE-cadherin, the expression of the most typical endothelial marker vWF and sensitivity to pro-inflammatory stimuli, as shown by induction of the expression of cell adhesion molecules (CAMs) by lipopolysaccharide (LPS). These data indicate that ECs growing on SPCL fiber-mesh scaffolds maintain a normal expression of ECspecific genes/proteins, indicating a cell compatibility and potential suitability of these scaffolds for the vascularization process in bone tissue engineering in vivo.